2016
DOI: 10.24276/rrecien2358-3088.2016.6.17.45-56
|View full text |Cite
|
Sign up to set email alerts
|

A importância do enfermeiro durante a reação transfusional aguda: revisão da literatura

Abstract: Resumo: Contextualizar a atuação do enfermeiro, suas capacidades técnicas e científicas frente à assistência de enfermagem na reação transfusional aguda, de acordo com a literatura científica. Trata-se de um estudo descritivo, do qual foram selecionados artigos nas seguintes bases de dados: SciELO.Org e LILACS. Para busca dos artigos, foram utilizados os seguintes descritores: Enfermagem, Reação e Transfusão Sanguínea. Para fins de análise, foram elaboradas 02 tabelas sendo: caracterização dos estudos e descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 6 publications
0
4
0
7
Order By: Relevance
“…7 This is a worrying scenario, since the greatest cause of deaths due to transfusion reaction is due to the acute hemolytic reaction as a consequence of the incompatibility of the ABO system. 8 It is evidenced that transfusion-associated ciculatory overload (TACO) and transfusionrelated acute lung injury, called transfusion related acute lung injury (TRALI), are also transfusion reactions that deserve to be highlighted, as they have a higher prevalence in surgical centers, these being one of the main sectors where blood transfusions occur, and its aggravating factor is similar symptomatology, however, with differentiated conduct. 3,9 It is revealed that studies involving nursing assistance to hemotherapy patients are scarce, since hemotherapy is a recent practice in Nursing.…”
Section: Original Articlementioning
confidence: 99%
See 2 more Smart Citations
“…7 This is a worrying scenario, since the greatest cause of deaths due to transfusion reaction is due to the acute hemolytic reaction as a consequence of the incompatibility of the ABO system. 8 It is evidenced that transfusion-associated ciculatory overload (TACO) and transfusionrelated acute lung injury, called transfusion related acute lung injury (TRALI), are also transfusion reactions that deserve to be highlighted, as they have a higher prevalence in surgical centers, these being one of the main sectors where blood transfusions occur, and its aggravating factor is similar symptomatology, however, with differentiated conduct. 3,9 It is revealed that studies involving nursing assistance to hemotherapy patients are scarce, since hemotherapy is a recent practice in Nursing.…”
Section: Original Articlementioning
confidence: 99%
“…It is necessary to study the knowledge of the professionals about it, considering the importance of the nurse in patient safety and the quality of the blood component. 8 In view of the relevance of the topic related to the recognition of a transfusion reaction, the knowledge of proper conduction, the need for notification and all the context that involves the work of the worker, which the study brings as a guiding question of research: "What is the knowledge of nursing professionals about the transfusion reaction in a small hospital in the municipality of Palmas/PR? ".…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…A transfusão sanguínea é um procedimento complexo, de grande importância na terapêutica moderna que se destina a administração de diversos produtos sanguíneos por via endovenosa. Requer conhecimento cientifico dos profissionais envolvidos no processo, visando a necessidade de cuidados especializados durante toda a terapia transfusional, desde a administração até as complicações agudas ou tardias (DE LIMA, et al, 2016).…”
Section: Introductionunclassified
“…Reações transfusionais são agravos ocorridos durante ou após a transfusão sanguínea e a ela relacionados. Sendo classificadas em: Incidentes transfusionais imediatos: no início da administração dos hemocomponentes ou até 24 horas após e Incidentes transfusionais tardios: após 24 horas da transfusão realizada (DE LIMA, et al, 2016).…”
Section: Introductionunclassified